Tegument protein control of latent herpesvirus establishment and animation - Penkert, Rhiannon R (BioMed Central, 2011)
Herpesviruses are successful pathogens that infect most vertebrates as well as at least one invertebrate species. Six of the eight human herpesviruses are widely distributed in the population. Herpesviral infections persist for the life of the infected host due in large part to the ability of these viruses to enter a non-productive, latent state in which viral gene expression is limited and immune detection and clearance is avoided. Periodically, the virus will reactivate and enter the lytic cycle, producing progeny virus that can spread within or to new hosts. Latency has been classically divided into establishment, maintenance, and reactivation phases. Here we focus on demonstrated and postulated molecular mechanisms leading to the establishment of latency for representative members of each human herpesvirus family. Maintenance and reactivation are also briefly discussed. In particular, the roles that tegument proteins may play during latency are highlighted. Finally, we introduce the term animation to describe the initiation of lytic phase gene expression from a latent herpesvirus genome, and discuss why this step should be separated, both molecularly and theoretically, from reactivation.